Financing to deposit ratio, dana pihak ketiga, modal sendiri, dan tingkat bagi hasil terhadap profitabilitas Bank Umum Syariah di Indonesia: Peran jumlah pembiayaan sebagai variabel moderasi - Larasati, Yustika Febi; Irkhami, Nafis (Journal of Accounting and Digital Finance, 2023)
This study aims to analyze the effect of Financing to Deposit Ratio (FDR), Third Party Funds (TPF), Equity, and Profit-Sharing Rate on profitability (ROA) with the amount of financing as a moderating variable at Islamic Commercial Bank in Indonesia for the period 2017-2021. The data used are secondary panel data from the annual reports of banks registered with the OJK, with data analysis using moderated regression analysis (MRA) and samples taken by purposive sampling. The study results indicate that FDR and TPF have a negative but insignificant effect on ROA, equity is not significant, and the profit-sharing rate has a significant positive effect on ROA. The amount of financing cannot moderate the relationship between FDR, TPF, and equity on ROA; instead, it negatively affects the relationship between the profit-sharing rate and ROA.